Efeitos da gramínea invasora Melinis minutiflora P. Beauv. sobre a vegetação nativa e solo de campo rupestre do Parque Estadual da Serra do Rola Moça, Minas Gerais, Brasil - Pâmella Cristina Dias Ribeiro (2016)
Biological invasions are one of the greatest threats to biodiversity. The Melinis minutiflora P. Beauv. (molasses grasses), is from Africa and became invasive in many regions of the world due their competitive and efficient strategies that inhibit the native species, often moving them and/or excluding them, in addition to changing many ecological processes of ecosystems. In Brazil, this invasion is a major threat to native flora, especially in protected areas. The Parque Estadual da Serra do Rola Moça (PESRM) is one of the most important preservation sites of Campos Rupestres over ironstone outcrop of rock fields (vegetation that occurs on rocky outcrops at altitudes greater than 900m, in the state of Minas Gerais). This region is seriously threatened by the invasion of M. minutiflora. Some native species of the family Fabaceae (legumes) showed different degrees of tolerance to invasive plants, being the Mimosa pogocephala Benth. the dominant legume species in the studied site. The effects of M. minutiflora invasion on native plants community was estimated by occupation index, the total abundance of families and species, species richness and composition of the plant community. For evaluate these purposes it was allocated in the field 15 plots of 4m2 with 5 treatments related to the level of Melinis minutiflora invasion, distributed in 3 blocks, resulting in a total of 45 plots. It was recorded 86 species belonging to 33 families and a high reduction over the diversity after the invasion. The high invasion levels was able to reduce the occupation of native species than 2%. Mimosa pogocephala showed resistance to the high density of invasion. Other species of the Fabaceae family, Malpighiaceae, Euphorbiaceae and Asteraceae showed also a high degree of tolerance to the invasive plant. M minutiflora shifted especially Poaceae family plants and, subsequently, the remaining families were compromised. These results showed that the number of individuals per species, given by the abundance, is an appropriate indicator to evaluate the invasion degree. SIMPER test confirmed that M. minutiflora promoted profound changes at the beginning of the invasion impeding the survival of the native. The results indicate that invasion process M. minutiflora in PESRM appear to be directed by a factor of soil nutrients.